26. Mapping of the cauda equina with free running and provoked EMG. Issue 9 (September 2016) - Gutierrez, Jorge
Abstract : Although intraoperative damage to nerve roots it's not as catastrophic as spinal cord injuries, damage to these structures could produce motor and sensory deficit, neuropathic pain, bladder and bowel dysfunction. Free-running EMG is considered a standard method for root monitoring given its ability to detect, in real time, trains or bursts of abnormal discharges that indicate possible ventral root damage. It's easy to use, not affected by anesthesia and has high sensitivity but low specificity. Given the myotomal overlapping multichannel recordings are required using preferably bipolar intramuscular electrodes. Triggered electromyography (tEMG) allows the surgeon to map viable neural tissue and to detect the proximity of instrumentation to nerve roots. tEMG has also been used as guidance during selective dorsal rhizotomy and it helps in the safe placement of pedicle screws. Bipolar stimulation is more selective and allows better spatial discrimination, a threshold higher than 6–8 mA (using a pulse duration of 0.1 ms) indicates very likely absence of functional tissue. Both methods have important limitations and should not be used alone but as a part of a multimodality monitoring plan including also somatosensory evoked potentials, transcranial electrical motor evoked potentials, H and sacral reflexes.